(untitled) - Satake, Nobio (New Jersey, 1990)
This book introduction about phenomena in language acquisition and primary data, learnability theory, BUD and other computational models, the whole constitution of BUD...
Keywords: Language acquisition,Am hiểu về ngôn ngữ; Data processing,Cơ sở dữ liệu